Analysis of Lithuanian credit default swaps - Kregzde, Arvydas; Murauskas, Gediminas (Journal of Business Economics and Management, 2015)
This paper studies international sovereign Credit Default Swaps (CDS) market focusing attention to the CDS of Central and East Europe. The main purpose of the study was to perform detail analysis of Lithuanian CDS in the global capital market. We compared the CDS markets of other countries and found some commonalities between them. We study the credit curve produced by CDS and volatility of CDS. A great attention is paid to investigate the relationship of CDS and the government bond market. Analysis of finding a leading role of CDS and the bond markets in the price discovering process is made. A leading market for different periods is found by using the Vector Error Correction model. Our main finding is that during the volatile period price discovery takes place in the bond market and in the calm period price discovery is observed in the CDS market. Disclosed relationship between CDS spreads and Eurobonds yield risk premium gives an additional decision making tool for sovereign debt managers.First published online: 29 Apr 2014